You are on page 1of 6

ADM formulation of general relativity


One possibility to approach quantum gravity is the hamiltonian formulation of general relativity1 .
As it first has been formulated as a complete theory by Arnowitt, Deser and Misner one therefore
often calles it the ADM formalism today. But in some book and lectures it is also referred to it as
the hamiltonian formulation, or foliation of general relativity.
Starting with
Gab = Rab gab R = Tab ()
the aim is to perform a Legendre transformation to obtain a Hamiltonian formulation of the
Einstein-Hilbert Lagrangian


We are going to use the metric signature ( + ++), latin indices iklj run from 1 to 3 and abcd from
0 to 3, where x0 = t. In addition we set = 1. To achieve our goal we will follow the roadmap
given below:
1. Foliate spacetime manifold into a series of spacelike hypersurfaces.
2. Re-express the Lagrangian in terms of hij , N and Ni .
3. Find the momentum conjugate to hij , N and Ni .
4. Perform a variation of the Hamiltonian with respect to N and Ni to obtain two constraint
equations, viewing N and Ni as Lagrange multipliers.
Putting all those steps together we will finally obtein the Hamiltonian constraint formulation of

Foliation of spacetime

One can show that an arbitrary globally hyperbolic manifold M can be foliated into a family of

Figure 1: Foliation of spacetime in general relativity

hypersurfaces of constant t, which we call t . Assuming spacetime (M, g) is of this topological
structure R we can split the metric into spatial and time components. On each hypersurface
of constant t we can now define a pure spatial metric hij , by:
hij = gij + ni nj ,


with unit normal vector ni of the hypersrface t . The unit normal vector is necessarily timelike
with lenght na na = 1, as the hypersurfaces are spacelike. Supposing the infinitesimal distance on a
hypersurface is given by hij (t, xi )dxi dxj , the proper time of a co-moving observer is differing from
the coordinate time by the lapse function N which yields:
d = N (t, xi )dt.
1 We

will refer to general relativity as relativity if not mentioned elsewise

The distance between two infinitasimally adjecent points on a hypersurface is given by

xi2 = xi1 N i (t, xi )dt,
where N a is called the shift vector . Physically the lapse function represents the rate of flow of
proper time with respect to t:
N = t n


and N a represents the movement tangential to the surface t

N i = hi j tj .


They allow us to sew two hypersurfaces together as illustrated in figure 1. In four dimensional
spacetime the line-element ist - as we remember - given by
ds2 = (coordinate distance)2 (proper time)2 .


Introducing our previous results we obtain for our line-element the expression:
ds2 = hij (dxi + N i dt)(dxj + N j dt) (N dt)2
= gab dxa dxb .


Using this result, the components of gab can be derived.

g00 = hij N i N j N 2 = Nj N j N 2



ga0 = hij N = Ni


gab = hij


g0b = hij N = Nj

It also is quite easy to see that

g =

detg = N 2 dethij = N h

hij , N i and N are the new variables defining the field since they contain the same information as
the original spacetime metric. As the next step the Lagrangian given above hast to be re-expressed
in terms of these variables.

The field equations in terms of the new variables

Now that we have definde the foliation of spacetime, we take the field variables to be hij , N i and
N . These lead to the relations2


h ij
N i


To be abled to find the time-derivative Lt hij we introduce the extrinsic curvature, which is defined
Kij := hki k nj =

Ln hij = N 1 (Lt hij LN hij ) .


2 When looking at those equations it is important to realize that the dot does not indicate a time-derivative.
Because of the canonical framework the diffeomorphism invariance of general relativity has to be maintained (e.g.
the system should be coordinate-independent). As time is defined differently in each coordinate-system it is not
suited for this approach. It is necessary to differentiate to the local time that is perpendicular to the hypersurface at
each point of it and this perpendicular direction is given by the field that describes time. Therefore the Lie-derivative
is used.

This definiton is analogous to the covariant derivative along a curve, which is nothing but the
parallel transport along a curve. It is possible to rewrite Einsteins field equations in terms of
this curvature and finally give the equations of motion refering to the variables (10) - (12). Well
accomplish those to things during the next pages, starting with the vaccum field equations.
As we already introduced a 3-dimensional metric, a number of quantities in 3 dimensions have to
be defined. Therefore first the curvature tensor is expressed in terms of a dual vector field and of
the derivative associated with hab . Starting with the 4-dimensional tensor
(a b b a )V c = Rc dab V d
we indentify the changes given below





Rd abc


Rd abc

and define

Rabc d d = (Da Db Db Da )c .


The operation Da is called the exterior derivative, is defined as

Dc T a1 ...ak b1 = ha1 d1 . . . hbl el hc hf f T d1 e1 ...el .


From this we obtain that

Da Db c = Da hb d hc e d c
= ha f hb g hc k f hdg hek d e


= ha f hb d hc e f d e + hc e Kab nd d e + hb d Kac ne d e
using the relation that
ha b hc d b hd e = ha b hc d b (gd e + nd ne ) = Kac ne ,


because b gd = 0 and ha b nd = Kad . One can calculate that in addition the following holds:
hb d ne d e = hb d d (ne e ) hb d e d ne = Kb e e


As the second term on the right-hand of Eq. (16) is symmetric in a and b it will vanisch in Eq.
(14). By this we finally achieve

Rabc d = ha f hb g hc k hd j Rf gk j Kac Kb d + Kbc Ka d


One can also conclude

Rabcd hac hbd = Rabcd (g ac + na nc )(g bd + nb nd )
= R + 2Rac na nc
a c

= 2Gac n n


Gab na nb =

Rabcd hab hcd
gdm Racb m hab hcd
(hdm nd nm )Racb m hab hcd
(hdm nd nm )hfa hgc hkb hm
Rf gk j + Kf k Kg j Kgk Kf j )hab hcb
j (
(hdm nd nm )hf k hgd hm
Rf gk j + Kf k Kg j Kgk Kf j )
j (
1 f k g (3)
h j ( Rf gk j + Kf k Kg j Kgk Kf j )
1 (3)
( R + K k k K j j Kjk K jk ) = 0

From the second line in Eq. (20) we can derive the Ricci scalar as
R = 2(Gab na nb Rab na nb )


If one now calculates Rab na nb in terms of the extrinsic curvature the Lagrangian densitiy can be

written, using L = gR.

Rab na nb = Racb b na nb
= na (a c c a )nc
= (a na )(c nc ) (c na )(a nc ) a (na c nc ) + a (na a nc )


= K 2 Kac K ac Divergence terms

In total we now have derived the Einstein field equations in vacuum depending the extrinsic
1 (3)
( R Kij K ij + K 2 )
Rij ni nj = K 2 Kij K ij

Gij ni nj =


Combining those two equations and attaching them into the Lagrangian yields

R + Kij K ij + K 2

1 2
= hN (3) R +
N (Lt hij LN hij )(Lt hij LN hij ) K i i K i i





and we are finally capable to deduce the equations of motion (the conjugate momenta):
Lt hij

1 2

= hN
N (Lt hij LN hij )
Lt hij

= hN N 1 K ij N 2 (Lt hij hij LN hij hij )2

1 ij
= hN (N K N 1 Khij )

= h(K ij Khij )

ij =


and furthermore
= 0.
N i

N =




Discussion of the Lagrange multipliers

We want to point out what the above found equations mean. Thereby N and N i turn out to be
Lagrange multipliers. To find out the means well have a look at a simple example of the classical
Hamiltonian to give an adequate answer:
Consider a pendulum with coordinates (x, y) and the normalization condition x2 + y 2 = l2 .
The Lagrangian for such a pendulum is, as we already know, given by L = 12 (x 2 + y 2 ) mgy
and the variation priciple leads to

S =

Ldt =

x +
y dt

Since x2 + y 2 = l2 the constraint (l2 x2 y 2 ) can be added without exerting a change in

action. If further on x, y and are considered dynamical variables
p =



always holds. As a conclusion of this results we gain, that if a constraint is hidden in a

Lagrangian, or the Hamiltonian for that matter, the conjugated momentum to the dynamical
variable (which displays a degree of freedom) turns out to be 0. The retrieved constraint then
is, that if the conjugated momentum is 0, also
= 0.


= 0 therefore are that these variables have to be constraints

The conclusion from L
= 0 and L
N i
of the system and are the so-called primary constraints.

The Hamiltonian and the Hamiltonian constraints

The Hamiltonian density can now be defined by the degrees of freedom hij :
H = ij h ij L
= ij (2Kij N + LN hij )

hN ((3) R + Kij K ij K 2 ).


For the exterior derivative holds

Di hjk = 0,


which is analogous to the covariant derivative c gab = 0. In addition the Lie-derivative of the
spatial metric can (in analogy to the Lie-derivative of spacetime metric) be written as
LV hij = Di Vj + Dj Vi .


By this we are abled to rewrite the Hamiltonian in terms of D and

the extrinsic curvature in terms of ij and hij :

kl hkl hij ij .
Kij = h1/2


and to do so well first give

This can be shown by inserting it into Eq. (25). The Hamiltonian thereby becomes

H = ij (2Kij N + Di Nj + Dj Ni ) hN ((3) R + Kij K ij K 2 )

= hN ((3) R Kij K ij + K 2 + 2h1/2 ij Kij ) + ij (Di Nj + Dj Ni )


We now further develop the right-hand side of Eq. (33). To do so we are going to need the following

Kij K ij = h1 ij ij kl hkl hij ij + 2

ij Kij = h1/2 ij ij kl hkl hij ij
K 2 = h1 2 .


If Eq. (34) is inserted into Eq. (33) it becomes

H = hN



ij h1 2


2Nj Di (h1/2 ij ) + 2Di (h1/2 Nj ij ).

The last terms build just a boundary term in the integral, used to obtain the Hamiltonian and can
therefore be ignored. According to this for Lagrange multipliers holds H
= 0, so that we get the
Hamilton constraint
= (3) R + h1 ij ij h1 2 = 0


and the diffeomorphism or Gauss constraint

h ij = 0.
= Di


Those to have in fact first been formulated by Dirac, which is why he should also be mentioned at
this point. Finally one can perform an analysis of the problems they raise and which can partly
be solved by introduction of new variables, the so-called Ashtekar variables.

Problems associated with the constraint equations

The now complete ADM formulation of general relativity can be quantized by a process introduced
by Dirac. For his one first calculates the Poisson-brackest
{hij (x), kl (y)} =

1 k l
i j + jk il 3 (x y)

and the variables turn into operators

hij h



As, following the constraint equations, H = 0 always holds the Schrodinger equation reduces to

= 0. Here we have

2 hNi
and therefore can conclude the Wheeler-De Witt equations


|i = 0

|i = 0.


The problem is that the first of those equations is ahighly singular functional differential equation
for which until now no physical solutions have been found.
There are of course other steps possible to be taken into quantum gravity as e.g. loops.